Media Pembelajaran Berbasis Teknologi Informasi dengan Power Point Interaktif dan Flip PDF Professional untuk Guru SMA/SMK - Reno Fernandes; Azwar Ananda; Amin Akbar; Emizal Amri; Rhavy Ferdyan; Monica Tiara (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Online learning and blended learning require teachers to prepare all learning materials in digital form that are easily accessible to students. However, student interaction, interest, and interest in the learning process is still low because the teacher uses information technology-based learning media that is not interactive. The implementation of this community service activity was prepared based on the willingness letter of the Regional VII Education Office Branch of West Sumatra No. 420/216/Cabdin.VII/KP-2022, which requires competency development for SMA/SMK teachers in designing information technology-based learning media or digital media in the learning process. The solution offered is a program to increase teacher competence in designing interactive technology-based or digital learning media and fostering student interest in the learning process. One form of learning media needed is interactive power points and digital-based teaching materials using flipPDF Professional. The forms of activities carried out are seminars and workshops. Service activities are carried out by looking at the teacher's initial knowledge regarding the learning media that will be developed. During this community service program teachers are facilitated and trained to design instructional media. The expected output is that teachers are able to produce interactive power points and FlipPDF Professional digital teaching materials in one Basic Competence (KD) for each subject in SMA/SMK.